TANTANGAN PELESTARIAN NILAI KEJUJURAN DALAM TRANSAKSI JUAL BELI PADA PLATFORM E-COMMERCE - Muhammad Rizky Ramadhan; Dinda Aulia Lestari (Yayasan An-Nur Meunara Baro, 2026)
The transition from traditional markets to e-commerce in Indonesia has brought great efficiency, yet simultaneously triggered a crisis of trust due to the prevalence of product mismatches and digital information manipulation. This study aims to map the challenges of preserving the value of honesty in online transactions and formulate strengthening strategies based on Islamic values. Using a qualitative descriptive approach with netnography on the Borneo Digital Hub community in Balikpapan. Data were analyzed through content analysis of digital interactions and platform policies. It was found that digital anonymity creates psychological effects that weaken the moral responsibility of sellers, triggering tadlis (hiding defects) and review manipulation. However, entrepreneurs who internalize the principles of Siddiq and Amanah proved to have a more sustainable reputation (branding). This study recommends integrating transparent platform features with Sharia economic literacy for MSME players. These results contribute to the development of an e-commerce model that prioritizes barakah and trust as the main pillars of the digital economy in Indonesia.